Research on genetic diversity of cassava (Manihot esculenta Crantz) based on DNA polymorphism on gpss1 gene - Thao, Nguyen Phuong; Mai, Nguyen Chi; Tuan, Phan Minh; Linh, Tran My; Lien, Le Quynh; Chung, Le Quang; Van, Nguyen Tuong (Academia Journal of Biology, 2015)
GBSS1 gene regulates the biosynthesis of starch in cassava, Manihot esculenta Crantz, and its allelic diversity relates to variation in their starch production. In this research, genetic diversity of the recent conserved cassava germplast was estimated based on DNA polymorphism of a targeted fragment on GPSS1 gene of 14 representatives selected from 44 cassava varieties, whose genetic diversity was previously determined with SSR markers. The results from analyses of boostrap values on Neighbor Joining tree, of genetic indice from DNAsp 4.10.9 software, and of typical mutated points of 612bp-fragments on GBSS1 gene of the studied varieties revealed high genetic diversity and were in agreement to previous analyses with SSR markers. All 14 varieties were separated into 3 clusters on Neighbor Joining tree, in accordance with the variation in tuber-starch percentage and fresh root yield between groups. All three groups showed high genetic diversity with 53-99% of bootstrap values, high genetic differentiation (Kst=0.74, χ2=28; P=0.036), high number of allele (A=9) and high allenic diversity (Ad=0.91). The varieties of each group had 2-5 typical alleles. Results of this study could be applied for estimation of effectiveness of cassava germplast conservation. Together with the relevant SSR markers, the typical alleles of GBSS1 gene of different groups could be used as additional markers for selection and breeding of cassava with high starch yield in their tubers.